Pemeriksaan Gula Darah Sewaktu Bagi Kader Asadana Semesta Tabanan - Putri, Desak Made Firsia Sastra; Apriani, Yenny; Supartha, Ardi (Jurnal Abdi Mahosada, 2024)
A person is more at risk of developing blood sugar disease (type 2 DM) due to the following factors. someone who is over 45 years old, has a family history of type 2 diabetes, rarely does physical activity or exercise, is overweight or obese, suffers from prediabetes, suffers from high cholesterol, and suffers from high blood pressure (hypertension). A blood sugar test is an examination that is absolutely necessary to diagnose type 1 or type 2 diabetes. The results of blood sugar measurements will show whether a person has diabetes or not. Patients must control their blood sugar in a disciplined manner through a healthy diet so that blood sugar does not increase above normal. The aim of this service to society is to determine current blood sugar levels and provide knowledge to Asadana Semesta Tabanan cadres. The solution given is to check blood sugar levels and provide information about DM disease. The results were that most were at normal values ​​and only six people had blood sugar above 200 mg/dl. It was concluded that it is important to carry out examinations and provide information about DM disease so that they carry out routine examinations